A practical fluorogenic substrate for high-throughput screening of glutathione S-transferase inhibitors1. Issue 57 (21st July 2015) - Fujikawa, Yuuta; Morisaki, Fumika; Ogura, Asami; Morohashi, Kana; Enya, Sora; Niwa, Ryusuke; Goto, Shinji; Kojima, Hirotatsu; Okabe, Takayoshi; Nagano, Tetsuo; Inoue, Hideshi
<x xml:space="preserve">Abstract</x> We report herein 3, 4-DNADCF, a pH less sensitive new fluorogenic substrate, for high-throughput screening of GST inhibitors.